KECENDERUNGAN NASIONALISASI PADA PELAYANAN JASA KEBANDARAUDARAAN DAN FUNGSI KEMANAN PENERBANGAN DI INDONESIA - TIARTO (Langit Biru: Jurnal Ilmiah Aviasi, 2012)
Currently, delivery of services at the airport airport affairs are still provided by state-owned PT. AP-I/PT.AP-II and small airports by the Technical Unit of the Directorate General of Civil Aviation. But after deregulation of the airline as a result of events of 11 September 2001 in Indonesia airport affairs policies are constantly changing from the previously more inclined to privatization to nationalization. Proof if the previous airport DGCA UPT that can finance themselves financially (cost recovery), automatically transformed into state-owned airport, but now no longer. Finally, new problems began to emerge for discussion, whether the process of privatization of airport affairs services that have spread it will bring the same end result with the nationalization of airport affairs services to heritage and history different from each airport, or the emergence of variations in service models airport affairs, especially in aviation security functions at the airport.